Trust as an effectiveness factor in interim management projects - Skowron-Mielnik, Beata; Sobiecki, Grzegorz (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
This article aims to define the concept of trust and the role it plays in implementing interim management (IM) projects and achieving results. Trust is one of three categories of effectiveness factors (next to knowledge and power) adopted for the purposes of our research on the effectiveness of IM. In this study two aspects of trust are explored: cognitive and affective. The research methodology is founded on a well-established grounded theory supported by systematically collected empirical data (four IM projects). Our respondents included clients/decision makers (a questionnaire and an interview), interim managers (an interview) and teams that cooperated with them (a questionnaire). The study shows that trust is significant in determining the other two categories of effectiveness factors in IM projects.